Active Therapeutic and Diagnostic Management of Acute Appendicitis in a Pregnant Woman During the First Trimester - Akramova, M.Yu.; Abdumajidov, A.Sh.; Zuparov, K.F.; Alimxanov, O.O.; Aslonov, Z.A. (Academia Open, 2026)
General Background: Acute appendicitis is a frequent cause of abdominal pain in women of reproductive age and presents diagnostic and therapeutic challenges during pregnancy due to anatomical and physiological changes. Specific Background: In the first trimester, symptoms may appear typical, yet clinical evaluation remains complex, requiring careful diagnostic and surgical decision-making to ensure maternal and fetal safety. Knowledge Gap: Despite established surgical approaches, the optimal management strategy for appendicitis in early pregnancy, particularly regarding minimally invasive techniques and multidisciplinary care, remains insufficiently detailed in clinical case-based evidence. Aims: This study aims to present a clinical case and evaluate diagnostic and therapeutic management of acute appendicitis in a pregnant woman during the first trimester. Results: A 28-year-old patient at 12 weeks of gestation underwent successful laparoscopic appendectomy following clinical, laboratory, and ultrasound diagnosis, with uneventful postoperative recovery and preserved pregnancy confirmed by follow-up. Novelty: The study highlights the integration of laparoscopic surgery with obstetric collaboration and tailored postoperative care in early pregnancy. Implications: Early diagnosis, interdisciplinary management, and minimally invasive intervention contribute to favorable maternal and fetal outcomes while preventing severe complications such as perforation and peritonitis. Highlights: • Early Surgical Intervention Prevented Progression to Severe Abdominal Complications • Multidisciplinary Coordination Ensured Safe Perioperative Management for Mother and Fetus • Minimally Invasive Approach Supported Rapid Recovery and Stable Gestational Continuation <section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-69c61923-cc6c-8320-9162-b3185518c5f4-0" data-testid="conversation-turn-4" data-scroll-anchor="true" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-10 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="6733b03c-8a96-40d7-9ae2-e2cf2171d9eb" data-turn-start-message="true" data-message-model-slug="gpt-5-3"> Keywords: Acute Appendicitis, Pregnancy, Laparoscopic Appendectomy, First Trimester, Surgical Management.